Sea turtles bycatch in the Adriatic Sea set net fisheries and possible hot‐spot identification. Issue 6 (12th July 2017) - Lucchetti, Alessandro; Vasapollo, Claudio; Virgili, Massimo
Abstract: Bycatch resulting from fishing activities is the main threat for the conservation of sea turtles in the Mediterranean Sea. Fixed nets are a matter of concern for sea turtles mainly in coastal areas during the neritic stage when both juvenile and adult life stages are affected. Mortality caused by entanglement in set nets is related to forced apnoea due to the high soak time of the nets and consequent drowning. This study investigated the loggerhead turtle bycatch in set net coastal fisheries in the northern Adriatic Sea (General Fisheries Commission for the Mediterranean Geographical Sub‐Area 17, [GSA 17]) through an interview‐based approach, to understand the potential contribution of these fisheries to the general decline of the sea turtle population. A second goal was to identify a possible hot‐spot turtle bycatch area through on‐board observations. The study estimates that more than 5400 turtles are caught in the west GSA 17 each year with the largest number in the summer. A hot‐spot for entanglement was also identified in an area located south of the River Po delta (41.5–69 m depth) during the summer. Sixty‐four turtles were caught over a period of 30 fishing days by either trammel nets and gillnets (0.7 and 0.5 turtle per km of net respectively) and was the greatest number that has been observed anywhere in the Mediterranean. Possible management strategies to reduce bycatch include technical modification to gear setting (such as reducing netting slack and using small meshes), bycatch reducer devices (such as LED UV), and area and seasonal gear restrictions to small‐scale fisheries in areas of greatest concern in the northern Adriatic Sea.